Productivity, competition and bank restructuring process - Vanesa Llorens; Alfredo Martín-Oliver; Vicente Salas-Fumas (SERIEs - Journal of the Spanish Economic Association, 2020)
This paper analyzes how differences in productivity across banks and the evolution of industry productivity over time might determine the intermediation costs and the restructuring process of the banking industry in the Great Recession. With data of Spanish banks, we find that less productive banks are more likely to exit than more productive banks, and that surviving banks acquire target banks in order to expand their branch network in local markets where they are underrepresented. Competition among banks contributes to the translation of industry productivity growth into lower interest rates of loans. Nonetheless, we find that the industry profit margin in loans increases during the period because of the modest industry productivity growth and the lower intensity of competition from branch closing.
Keywords: G21; 330; Banks; Restructuring; Interest rates